Modeling Of Generator Neutral Ground System Using Labview 2017 Application IEEE std C62.92.2TM - muhammad fadlan siregar; Ayu Fitriani; Syafriwel; Catra Indra Cahyadi; M. Fitra Zambak; Suprianto (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
The generator is a device for an important source of electrical energy, so the continuity of the generator operation must be maintained and well controlled, in controlling the grounding on the generator can use in control with software such as MATLAB and Modeling the design of the grid grounding system using LabView 2017, Determination of the grounding system for the neutral value of the generator through the distribution transformer, can be done through manual calculation. The use of many parameters considered in the calculation to obtain appropriate and measurable results there is a possibility of repeated calculations. This is very difficult and causes a large difference in calculation results. Therefore, a computer-based computing system is needed to overcome problems like this. Several papers have developed calculations of the amount of generator neutral grounding required that consider the voltage level, short circuit fault current and ground fault protection system. This paper discusses modeling and simulation in designing generator neutral grounding using LabView 2017 application. The goal is to be easier, faster and more accurate. As an implementation of modeling, data from std C62.92.2TM-2017 is used.